2019
DOI: 10.1080/02699931.2019.1634003
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving emotion and sex from the body: evidence from the Garner task for independent processes

Abstract: Hawliau Cyffredinol / General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research.• You may not further distribute the material or use it for any profit-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 72 publications
3
19
3
Order By: Relevance
“…In both Zhou and Liu (2013)'s and our data, gender recognition was easier than emotion recognition, thus arguing against the possibility that the asymmetry between emotion and gender conflict could be due to a mismatch in task difficulty. Furthermore, interference from automatic processing is expected to be higher for more easily encoded and, thus, more salient features (Atkinson et al, 2005;Gandolfo and Downing, 2019). In contrast, we found that the more difficult-to-encode dimension (i.e., emotion) interfered with the easier one (i.e., gender), thus making it unlikely, albeit not ruling out, that the asymmetry between emotion and gender conflict was due to differential speed of processing.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In both Zhou and Liu (2013)'s and our data, gender recognition was easier than emotion recognition, thus arguing against the possibility that the asymmetry between emotion and gender conflict could be due to a mismatch in task difficulty. Furthermore, interference from automatic processing is expected to be higher for more easily encoded and, thus, more salient features (Atkinson et al, 2005;Gandolfo and Downing, 2019). In contrast, we found that the more difficult-to-encode dimension (i.e., emotion) interfered with the easier one (i.e., gender), thus making it unlikely, albeit not ruling out, that the asymmetry between emotion and gender conflict was due to differential speed of processing.…”
Section: Discussioncontrasting
confidence: 62%
“…The human visual system is highly sensitive to both emotion (Meeren et al, 2005) and gender cues (Bruce et al, 1993;Johnson and Tassinary, 2005), either conveyed by faces or bodies. Furthermore, the perception of these two salient cues seems highly interdependent, as shown by the interference exerted by variations of one dimension (i.e., gender) while recognizing the other (e.g., emotion; the so-called Garner interference effect; Gilboa-Schechtman et al, 2004;Atkinson et al, 2005;Becker, 2017; but see Gandolfo and Downing, 2019). This reveals the difficulties of the attentional control system in filtering out gender or emotional cues when the main task is focused on emotion or gender, respectively.…”
mentioning
confidence: 99%
“…The adult body's appearance carries strong signals about sex that are attended by observers (Gandolfo & Downing 2019a;Hewig et al, 2008;Johnson & Tassinary, 2005;Johnstone & Downing, 2017;Matsumoto et al, 2017;Nummenmaa et al, 2012). Judgments of sex from the shape and movements of others' bodies are generally highly efficient, even for impoverished stimuli (D'Argenio et al, 2020;Gandolfo & Downing, 2019b;Gaetano et al, 2014;Johnson & Tassinary, 2005;Kozlowski & Cutting, 1977;Mather & Murdoch, 1994;Palumbo et al, 2013;Runeson & Frykholm, 1983) although they are also subject to the influence of expectations (e.g. Johnson et al, 2011) and recent perceptual experience (Alexi et al, 2018).…”
Section: Visual Perception Of Sexmentioning
confidence: 99%
“…The validity in interpreting asymmetric Garner interference as integral processing is dependent on an assumption that response latencies at baseline between scene shape and texture are not significantly different. If one scene feature (e.g., shape) is processed faster than the other (e.g., texture) at baseline, then the interference observed in texture processing (but not shape processing) could be partially explained by the serial processing of these features (Algom & Fitousi, 2016;Gandolfo & Downing, 2020;Garner, 1976;Johnstone & Downing, 2017;Schweinberger et al, 1999). In a serial-processing hypothesis, the faster the first feature is perceptually represented, the more potential it has to interfere with the processing of the second feature, thereby increasing Garner interference.…”
Section: Discussionmentioning
confidence: 99%
“…If participants can easily ignore changes in the irrelevant feature (i.e., no changes in response latency and classification accuracy between baseline and filtering trials) when classifying the relevant one, then these features are said to be processed independently and are labeled as separable dimensions. Examples of known separable dimensions include the position of lines and their luminance contrast (Shechter & Hochstein, 1992), the color and texture of objects (Cant, Large, McCall, & Goodale, 2008), and the sex and emotion of bodies (Gandolfo & Downing, 2020). If, however, participants have worse performance in the filtering trials (i.e., increased response latency or a greater number of classification errors) compared with the baseline, then these features are not processed independently and are said to be integral feature dimensions, which demonstrate Garner interference.…”
Section: Introductionmentioning
confidence: 99%